1998
DOI: 10.1111/j.1439-0442.1998.tb00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematological, Biochemical and Toxicological Investigations in Spontaneous Cases with Different Frequency of Porcine Nephropathy in Bulgaria

Abstract: Haematological, biochemical and toxicological investigations of blood and urine of normally slaughtered pigs exhibiting different frequency (1-2 O/o, 10-20 % and 5 M 0 ' 1 . ) of changes characterized as "enlarged mottled kidneys"; at the slaughtering meat inspection were carried out to elucidate the nature of nephropathies encountered in Bulgaria. A content of ochratoxin A, higher in the spring than the autumn, was found in the serum and urine samples. The mean contamination levels of ochratoxin A in consumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 13 publications
5
51
1
Order By: Relevance
“…Keeping in mind the low contamination levels of OTA in serum, tissue and feed of chickens with nephropathy, we can conclude that the chicken nephropathy, similarly to porcine nephropathy in Bulgaria [26,27], may have a multitoxin or multifactor aetiology, because it cannot be explained by the concentration/action of OTA alone. Detailed investigations have to be made to identify the cause of nephropathy in chickens.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Keeping in mind the low contamination levels of OTA in serum, tissue and feed of chickens with nephropathy, we can conclude that the chicken nephropathy, similarly to porcine nephropathy in Bulgaria [26,27], may have a multitoxin or multifactor aetiology, because it cannot be explained by the concentration/action of OTA alone. Detailed investigations have to be made to identify the cause of nephropathy in chickens.…”
Section: Discussionmentioning
confidence: 92%
“…While agreeing that the most important toxicological target of OTA in the pig is the kidney, the principal descriptions of the pathology of MNC vary considerably. Moreover, the clinico-morphological picture of spontaneous MNC in Bulgaria differs significantly from the classical description of the nephropathy made in Scandinavia [5] and is also encountered in the same regions of the country where a mycotoxic porcine nephropathy is evident, which supposes the same multicausal nature [26,27]. Therefore, it was necessary to elucidate the aetiology of this nephropathy and to describe in full its clinicomorphological picture.…”
Section: Introductionmentioning
confidence: 93%
“…Studies with pigs about blood glucose levels after OTA toxication are contradictory (28)(29)(30)(31). When rabbits fed with 1 and 2 ppm OTA contaminated food, a decrease in blood glucose level observed after 3 weeks and at week 8, blood glucose level was half of the control group (32).…”
Section: Discussionmentioning
confidence: 99%
“…OTA exhibits nephrotoxic (STOEV et al 1998), teratogenic, hepatotoxic (KUIPER-GOODMAN & SCOTT 1989), genotoxic (CREPPY et al 1985 and immunotoxic (LEA et al 1989) effects which were observed mainly in animals. OTA has been linked also with a human disease -Balkan endemic nephropathy (CASTEGNARO et al 1987).…”
Section: Discussionmentioning
confidence: 99%